IKLAN OBAT KESEHATAN PADA SURAT KABAR LOKAL BINTANG BORNEO EDISI JANUARI-MARET 1929 - Darmawati, Darmawati; Azmi, Muhammad; Kusumawijaya, Rizal Izmi (History Education Department, Universitas Mulawarman, 2023)
Medicines are an important element in health services. In order to guarantee the availability of medicines, effective and efficient medicine management is needed which is supported by financial resources, human resources, information management, facilities and infrastructure. The health needs of the community are exploited by health service providers by advertising their health services in the mass media. Advertisements offering health services are increasingly widespread in print media, local radio and television. In print media, they generally advertise in the form of classified ads (small advertisements) whose rates are relatively different for each drug. There are quite a lot of advertisers every day in certain newspapers offering various medicines such as Sanatogen, Kalzan, Aspirin, Abdijsiroop, Purol and so on. This research, which uses a case study method with a qualitative approach, aims to find out regulations regarding health service advertising and health service practices that are advertised through advertisements in the local newspaper Bintang Borneo.